Biocatalytic Synthesis of the Anti‐diabetes Agent‐corosolic Acid by Whole Cells of Microorganisms. Issue 10 (7th September 2015) - Fu, Shaobin; Meng, Qingfeng; Long, Shu‐an; Zhang, Yun; Sun, Di‐an; Wei, Gang
Abstract Diabetes is one of the most prevalent and costly global diseases. For diabetes, frequent insulin treatment and synthetic drugs are very expensive and may cause unwanted side effects. Corosolic acid (CA), a natural product, was reported to be efficient in the treatment of diabetes, meanwhile without induction of anti‐insulin antibodies and obesity. The preparation of CA attracted many researchers in the world. This study investigated the biocatalytic synthesis method of CA from ursolic acid by Streptomyces griseus subsp. griseus 4.18. LCMS analysis demonstrated that 5 day, 125 μg/mL substrate, pH=9 and 10% strain concentration were the appropriate conditions. It is estimated that biocatalysis will contribute to the development of green and sustainable synthetic processes with less time‐consuming and more environmentally friendly.